2022
DOI: 10.3390/jmse10121902
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Validation of Two Tidal Sand Wave Models: A Case Study of The Netherlands Continental Shelf

Abstract: Tidal sand waves form a dynamic bed pattern, widely occurring in shallow shelf seas such as the North Sea. Their importance to coastal engineering has inspired many advances in process-based sand wave modelling, aimed at explaining physical mechanisms in the formation stage (‘linear regime’) and capturing the finite amplitude evolution to equilibrium states (‘nonlinear regime’). However, systematic validation of particularly the nonlinear sand wave models is still lacking. Here, we perform a two-step calibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In the current settings, 100 years of simulation time takes about 1 month on an intel Xeon 2.10 GHz Linux computer. Several 2DV finite‐height studies have suggested calibrations to obtain a better match with observations (Campmans et al., 2022; Krabbendam et al., 2021), but the long simulation time restricts the number of runs that can be done.…”
Section: Discussionmentioning
confidence: 99%
“…In the current settings, 100 years of simulation time takes about 1 month on an intel Xeon 2.10 GHz Linux computer. Several 2DV finite‐height studies have suggested calibrations to obtain a better match with observations (Campmans et al., 2022; Krabbendam et al., 2021), but the long simulation time restricts the number of runs that can be done.…”
Section: Discussionmentioning
confidence: 99%
“…In the current settings, 100 years of simulation time takes about 1 month on an intel Xeon 2.10 GHz Linux computer. Several 2DV finite-height studies have suggested calibrations to obtain a better match with observations (Campmans et al, 2022;Krabbendam et al, 2021), but the long simulation time restricts the number of runs that can be done.…”
Section: Remarks About the Design Of The Sand Wave Modelmentioning
confidence: 99%
“…In the current settings, 100 years of simulation time takes about 1 month on an intel Xeon 2.10 GHz Linux computer. Several 2DV finite-height studies have suggested calibrations to obtain a better match with observations Campmans et al, 2022), but the long simulation time restricts the number of runs that can be done.…”
Section: Remarks About the Design Of The Sand Wave Modelmentioning
confidence: 99%